Passive Thermography Measurement of Damage Depth During Composites Load Testing - Zalameda, Joseph N.; Winfree, William P. (Frontiers in Mechanical Engineering, 2021)
Passive thermography is commonly used for composites load testing to detect damage formation as a function of the applied load. The advantages of passive thermography are real time implementation, large area coverage, and noncontact measurement. Passive thermography is able to detect the damage location and size, however, damage depth has been a challenge. Recent work has shown that damage formation during loading produces heating that is composed of two heat generation components. The first component is an instantaneous thermal response due to an irreversible thermoelastic strain release due to rapid damage formation. The second component observed is mechanical heating, at the interface of failure, due to fracture damage that produces a transient rise in temperature as a function of damage depth. The first component defines the thermal start time for the transient response. A one-dimensional thermal model is presented and fitted to the data pixel by pixel, to produce imagery of the damage depth. The results are compared to ultrasonic and X-ray CT data.